2012
DOI: 10.3389/fnhum.2012.00244
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sensory stimulation therapy improves hand function and restores cortical responsiveness in patients with chronic cerebral lesions. Three single case studies

Abstract: Rehabilitation of sensorimotor impairment resulting from cerebral lesion (CL) utilizes task specific training and massed practice to drive reorganization and sensorimotor improvement due to induction of neuroplasticity mechanisms. Loss of sensory abilities often complicates recovery, and thus the individual's ability to use the affected body part for functional tasks. Therefore, the development of additional and alternative approaches that supplement, enhance, or even replace conventional training procedures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 67 publications
2
34
0
Order By: Relevance
“…These important and unexpected findings arein agreement with other recent findings revealing that many aspects of the brain remain plastic even at adulthood [38]. They are also consistent with several other studies in post stroke patients [39], [40], [41]. In the current study, patients were treated only with HBOT without any additional guided training and/or practice.…”
Section: Discussionsupporting
confidence: 94%
“…These important and unexpected findings arein agreement with other recent findings revealing that many aspects of the brain remain plastic even at adulthood [38]. They are also consistent with several other studies in post stroke patients [39], [40], [41]. In the current study, patients were treated only with HBOT without any additional guided training and/or practice.…”
Section: Discussionsupporting
confidence: 94%
“…Five studies reported the use of electrical stimulation in adults after stroke . Electrical stimulation is a technique that uses electrical currents to stimulate peripheral nerves after neurological injury.…”
Section: Methodsmentioning
confidence: 99%
“…Fourth, previous trials with stimulation in sensory cortex achieved improvement of hand function in patients with chronic cerebral lesions. 41 Based on these reports, the SPC is likely to be a promising alternative target for post-stroke cortical stimulation. This study demonstrated that SPC stimulation promoted recovery of motor function after infarct lesioning of PLIC for both the SSG and the WSG.…”
Section: Discussionmentioning
confidence: 99%